Physical Functioning and Opioid use in Patients with Neuropathic Pain. Issue 7 (3rd February 2015) - Bostick, Geoff P.; Toth, Cory; Carr, Eloise C.J.; Stitt, Larry W.; Morley‐Forster, Patricia; Clark, Alexander J.; Lynch, Mary; Gordon, Allan; Nathan, Howard; Smyth, Catherine; Ware, Mark A.; Moulin, Dwight E.
Abstract: Objective: To evaluate the association between opioid dosage and ongoing therapy with physical function and disability in patients with neuropathic pain (NeP). Design: Secondary analysis of a prospective cohort. Setting: Multicenter clinical NeP registry. Subjects: Seven hundred eighty‐nine patients treated for various NeP diagnoses. Methods: The following measures were included: dependent variables. 12‐month self‐reported physical function (pain disability index [PDI] and medical outcomes study short form‐12 physical function [PCSS‐12]); independent variables: baseline opioid dose (none, ≤200 mg and >200 mg of morphine equivalent), ongoing opioid use; potential confounding variables: age, sex, baseline pain intensity, and psychological distress (profile of mood states). Analysis of covariance models was created to examine the relationship between opioid therapy and both physical functioning outcomes with adjustment for confounding. Results: Complete data was available for 535 patients (68%). Compared with the lower and high dose opioid groups, NeP patients not taking opioids had statistically lower disability and higher physical functioning scores, after adjusting for disease severity. Compared with patients prescribed opioid therapy on an ongoing basis, NeP patients who were not prescribed had statistically lower disability and higher physical functioning scores, after adjusting for disease severity. Improvements in disability and physical functioning scores from baseline and 12‐months in all groups were modest and may not be clinically significant. Conclusions: Physical functioning and disability did not improve in patients with NeP who were prescribed opioids compared with those who are not prescribed, even after adjusting for disease severity.